PARALLEL SURFACES TO S-TANGENT SURFACES OF BIHARMONIC S-CURVES ACCORDING TO SABBAN FRAME IN HEISENBERG GROUP HEIS3 - Korpinar, Talat; Turhan, Essin (Editura Bibliotheca-Bibliotheca Publ House, 2012)
In this paper, we study parallel surfaces to. (S-)tangent surfaces according to Sabban frame in the Heisenberg group Heis(3). We characterize parallel surfaces to tangent surfaces of the biharmonic curves in terms of their geodesic curvature in the Heisenberg group Heis(3). Finally, we find explicit parametric equations of parallel surfaces. to (S-)tangent surfaces according to Sabban Frame.
Keywords: Biharmonic curve; Heisenberg group; Tangent surface